Avaliação da concentração de metais em peixes de diferentes níveis tróficos ocorrentes no Rio das Antas e no Rio Tega - RS - Angheben, Fernanda Marcon (My University, 2019)
The release of heavy metals into the aquatic environment causes a number of problems for this ecosystem particularly in regard to bioaccumulation and biomagnification in the trophic chain. In this context, the aim of this study was to analyze the concentration of lead (Pb), copper (Cu), chromium (Cr), mercury (Hg), nickel (Ni) and zinc (Zn) metals in the muscle tissue of native fish. of theTega and Antas rivers. The influence of the Tega River on the Antas River in relation to the concentration of metals in fish was evaluated due to the potential contamination by metal-mechanic industries installed in the contribution basin. The metals were also evaluated in relation to the trophic position of the target fish (Astyanax sp, Rhandia quelem, Loricariichtys anus, Hemiancistrus punctulatus, Hypostomus commersoni). Metal analysis was performed by inductively coupled plasma optical emission spectrometry (ICP-OES). The results showed a high level of chromium concentration in all collected individuals, showing the contamination of the aquatic biota and risks to the consuming population of these species. Zinc concentration was high only in the Tega River lambaris (Astyanax sp) samples. Copper and nickel levels are below the limits established by the Ministry of Health, through Anvisa's RDC No. 42/2013 and Decree 55871/65, in all samples analyzed, while mercury and lead did not reach the detection limits of the equipment. Because they are metal compounds with cumulative capacity, they can affect human health when fish are consumed. Analysis detected the presence of copper and nickel in muscle tissue. However, mercury and lead were not found in these tissues. It was also evidenced that the chromium metal presented bioaccumulation in detritivorous individuals of the Antas and Tega Rivers, presenting similar concentrations. Copper and nickel metals did not show significant concentration differences in comparison with the target species. Zinc presented different concentrations in omnivorous individuals from the Antas River. In the Tega River, the copper, nickel and zinc metals showed significantvalues only for omnivores, showing greater bioaccumulation of these metals in these individuals.
O lançamento de metais pesados no meio aquático causa uma série de problemas para esse ecossistema particularmente no que tange a bioacumulação e a biomagnificação na cadeia trófica. Neste contexto, o objetivo desse estudo foi de analisar a concentração dos metais chumbo (Pb), cobre (Cu), cromo (Cr), mercúrio (Hg), níquel (Ni) e zinco (Zn) no tecido muscular de peixes nativos dos Rios Tega e Antas. Avaliou-se a influência do Rio Tega sobre Rio das Antas em relação a concentração de metais nos peixes devido a potencialidade de contaminação por indústrias metal-mecânicas instaladas na bacia de contribuição do mesmo. Os metais foram avaliados ainda em relação à posição trófica dos peixes alvo (Astyanax sp, Rhandia quelem, Loricariichtys anus, Hemiancistrus punctulatus, Hypostomus commersoni). As análises de metais foram realizadas por espectrometria de emissão ótica por plasma acoplado indutivamente (ICP-OES). Os resultados evidenciaram alto nível de concentração de cromo em todos os indivíduos coletados, evidenciando a contaminação da biota aquática e riscos para a população consumidora dessas espécies. A concentração de zinco apresentou valores elevados somente nas amostras de lambaris (Astyanax sp) do Rio Tega, Os níveis de cobre e níquel encontram-se abaixo do limites estabelecidos pelo Ministério da Saúde, através da RDC nº 42/2013 da Anvisa e do Decreto 55871/65, em todas as amostras analisadas, enquanto mercúrio e chumbo não alcançaram os limites de detecção do equipamento. Por se tratar de compostos metálicos com capacidade cumulativa estes podem afetar a saúde humana quando os peixes são consumidos. As análises detectaram a presença de cobre e níquel no tecido muscular não sendo evidenciados nesse tecido o mercúrio e o chumbo os quais podem estar acumulados em outros tecidos. Evidenciou-se ainda que o metal cromo apresentou bioacumulação nos indivíduos detritívoros do Rio das Antas e no Rio Tega, apresentando concentrações semelhantes. Os metais cobre e níquel não apresentaram diferenças significativas de concentração entre as espécies alvo. O zinco por sua vez apresentou diferentes concentrações nos indivíduos onívoros oriundos do Rio das Antas. Já no Rio Tega, os metais cobre, níquel e zinco apresentaram valores significativos somente para onívoros demonstrando maior bioacumulação desses metais nesses indivíduos.
Keywords: Peixes de água doce; Metais; Metais - Indústria; Antas, Rio, Vale (RS); Tega, Rio; Freshwater fishes; Metals; Metals - Industry; Antas Valley (Brazil); Tega, Rio (Brazil)